ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM TERHADAP PENGELOLAAN MANAJEMEN KEUANGAN (Studi Pada KJSA dan KJUDM Kecamatan Seberida Kabupaten Indragiri Hulu Periode 2016-2020) - Teteh Muliajati; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine and analyze the comparison of financial performance in Savings and Loans Cooperatives (Studies on Service Cooperatives in Manunggal Village, Bandar Padang Village, Seberida District and Prosperous Palm Service Cooperatives, Titian Resak Village, Seberida District, Indragiri Hulu Regency during the 2016-2020 period) based on the liquidity ratio, solvency ratio, and profitability ratio. and to find out the fulfillment of cooperative financial performance standards based on liquidity ratios, solvency ratios, profitability ratios for the period 2016-2020 using financial ratios Current Ratio, Cash Ratio, Total Asset To Debt Ratio, Net Worth To Debt Ratio, Profitability Ratio and ROA.This study uses secondary data in the form of data obtained by the author from the financial statements of the Service Cooperative Unit in Manunggal Village, Bandar Padang Village, Seberida District and the Sejahtera Sawit Services Cooperative, Titian Resak Village, Seberida District, Indragiri Hulu Regency which was obtained from the offices of the two cooperatives, the data needed by researchers for liquidity analysis. , solvency, and profitability. The results of the analysis show that the analysis of the financial statements of the Service Cooperative Unit, Manunggal Village, Bandar Padang Village, Seberida District, Indragiri Hulu Regency for the 2016-2020 period based on the Liquidity Ratio, the Current Ratio and Cash Ratio get the title "Not Good, the Solvency Ratio in the Total Asset To Debt Ratio Rastio gets the "Good" predicate, the Net Worth To Debt Ratio gets the "Not Good" predicate and the Profitability Ratio in the Equity Profitability Ratio and ROA gets the "Not Good" predicate. While the results of the analysis of the financial statements of the Prosperous Palm Oil Services Cooperative, Titian Resak Village, Seberida District, Indragiri Hulu Regency for the 2016-2020 period based on the Liquidity Ratio, the Current Ratio and Cash Ratio received the title "Not Good". The Solvency Ratio in the Total Assets To Debt ratio Rastio got the "Very Good" predicate, the Net Worth To Debt Ratio got the "Very Good" predicate and the Profitability Ratio in the Own Capital Profitability Ratio and ROA got the "Not Good" predicate.Based on the results of the independent sample T-test, there were significant differences in the ratios of TATDR and NWTDR, and there were no significant differences in the ratios of CR, CSR, RMS and ROA.                                                                                                                         Keywords: Comparison of Financial Performance, Liquidity, Solvency and Profitability.